Research progress in high-temperature infrared stealth materials - GUO Jincheng; REN Sue; CHEN Yanfei (Cailiao gongcheng)
Infrared radiation at the hot-section of the aero engine is easily detected by infrared detectors， which is not conducive to aircraft service in a complex monitoring environment. How to reduce the infrared radiation characteristics of high-temperature parts of aero engine and improve the high-temperature infrared stealth performance of the aero engine is a difficult problem that needs to be solved. This paper discusses the infrared stealth mechanisms and research status of metal-based， inorganic non-metallic， and structural infrared stealth materials with potential applications in high-temperature environments. It also highlights the future development trends for high-temperature infrared stealth materials， including the need for further investigation into the failure mechanisms of these materials， the integration of temperature control methods to meet higher-temperature stealth requirements， and the necessity to develop comprehensive stealth performance to ensure the capability of aircraft to remain stealthy in complex environments.